Sunscreen Use among Students of the Faculty of Medicine YARSI University - Wisye Rizqia Amalia; Mirfat, Mirfat (Junior Medical Journal, 2024)
Introduction: Exposure to sunlight carries harmful to potentially dangerous effects. Protection against ultraviolet (UV) radiation can be achieved through physical and chemical methods by using sunscreen. Sunscreen is a chemical product that reflects UV radiation, thereby weakening the intensity of UV before it penetrates the skin. The use of broad-spectrum sunscreen with SPF 30 or higher is recommended in any situation. While numerous studies have been conducted worldwide regarding sunscreen usage, only a limited number have been conducted in Indonesia. This research aims to investigate the utilization of sunscreen among students of the Faculty of Medicine, YARSI University. Method: An analytic study utilizing a cross-sectional design was conducted to investigate sunscreen usage among students of the Faculty of Medicine, YARSI University. The random sampling technique was used to determine the sample size and the sample proportion was divided based on the year of enrollment using cluster sampling technique. The measurement instrument used was a questionnaire in the form of a Google form. Result: The total number of respondents in this study is 317 students from the Faculty of Medicine, YARSI University. The use of sunscreen was reported by 292 students. The factor that significantly influenced this result was the female gender (P value 0,000; OR 0,069). 90,9% of the students used methods of sun protection other than sunscreen. 70,3% of the students used broad-spectrum sunscreen, while 56,5% used sunscreen with SPF 31-50. However, 45,1% of the students still applied sunscreen less than 10 minutes before going outside and 41,6% students did not reapply sunscreen. Conclusion: The use of sunscreen among students of the Faculty of Medicine, YARSI University, revealed that nearly all students, 292 in total (92.1%), used sunscreen. However, there were still discrepancies in terms of the body parts applied, dosage, timing of application before going outside, and frequency of reapplication. The factor influencing sunscreen use was gender, specifically female (P value < 0.05).